EFEKTIVITAS SUPERVISI AKADEMIK BERBASIS REFLEKSI DALAM MENINGKATKAN PEMBELAJARAN MENDALAM (DEEP LEARNING) GURU SEKOLAH DASAR: SUATU TINJAUAN LITERATUR SISTEMATIS - Karis; Ngabiyanto; Avrilianda, Decky; Widiarti, Nuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of reflection-based academic supervision in improving elementary school teachers’ ability to implement deep learning. The method used was a Systematic Literature Review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. The literature search was conducted using the Google Scholar, ERIC, and Scopus databases, as well as accredited national journal portals, covering publications from 2021 to 2026. Of the total 387 identified articles, 25 met the inclusion criteria and were analyzed thematically. The review results indicate that reflection-based academic supervision, implemented through the stages of pre-observation dialogue, classroom observation, and reflective post-observation discussions, is capable of enhancing teachers’ pedagogical awareness, encouraging changes in teaching practices toward more meaningful approaches, and facilitating the application of deep learning elements such as critical thinking, collaboration, creativity, and communication. The implications of this study underscore the importance of reorienting academic supervision from an administrative-evaluative approach toward a sustainable reflective coaching approach to support learning transformation in elementary schools.